1999
DOI: 10.1074/jbc.274.10.6432
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Heparin-binding Sites in Native Vitronectin

Abstract: A recombinant polypeptide corresponding to the C-terminal 129 amino acids of vitronectin exhibits heparin-binding affinity that is comparable to that of full-length vitronectin and is equally effective at neutralizing heparin anticoagulant activity. Results from this broad experimental approach argue that the behavior of the primary site is sufficient to account for the heparin binding activity of vitronectin and support an exposed orientation for the site in the structure of the native protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…This result suggests that these 12 amino-acids represent the major high affinity binding site for heparin in vitronectin, and it is consistent with data from Gibson et al (24) who have demonstrated through biophysical studies the existence of only one heparin binding domain in vitronectin; and data from Francois et al (23) who have shown by FRET (fluorescence resonance energy transfer) analysis that a peptide consisting of amino acids 347-361 exhibits heparin binding kinetics similar to intact vitronectin. Since our binding experiments used nanogram quantities of heparin, we cannot however, rule out the possibility that vitronectin may contain additional low affinity heparin binding sites.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result suggests that these 12 amino-acids represent the major high affinity binding site for heparin in vitronectin, and it is consistent with data from Gibson et al (24) who have demonstrated through biophysical studies the existence of only one heparin binding domain in vitronectin; and data from Francois et al (23) who have shown by FRET (fluorescence resonance energy transfer) analysis that a peptide consisting of amino acids 347-361 exhibits heparin binding kinetics similar to intact vitronectin. Since our binding experiments used nanogram quantities of heparin, we cannot however, rule out the possibility that vitronectin may contain additional low affinity heparin binding sites.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that peptides derived from regions within vitronectin's heparin binding domain exhibit variable levels of heparin binding (14,24,39,43,77). A majority of two heparin binding consensus sequences (5) comprise a previously described 12 amino acid "basic domain" within vitronectin's heparin binding domain (84).…”
Section: Vitronectin's Basic Domain Is a Proteoglycan Binding And Hepmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining the binding sites for these various biomolecules, along with determining the molecular mechanism of regulation, constitutes an active area of research on the protein. Work to date has focused on binding sites for several ligands, including heparin, PAI-1, 1 and integrins; a working model representing the domain structure of vitronectin has been recently reported from this laboratory (5).…”
mentioning
confidence: 99%
“…Purification and Labeling of Vitronectin-Monomeric vitronectin was purified from human plasma as described previously (38,39). For multiwavelength studies, vitronectin was labeled with fluorescein isothiocyanate using a FluoReporterÂź protein labeling kit (Molecular Probes, Inc., Eugene, OR) that labels primary amines.…”
Section: Methodsmentioning
confidence: 99%